2019
DOI: 10.1016/j.neubiorev.2019.02.017
|View full text |Cite
|
Sign up to set email alerts
|

Love is analogous to money in human brain: Coordinate-based and functional connectivity meta-analyses of social and monetary reward anticipation

Abstract: Both social and material rewards play a crucial role in daily life and function as strong incentives for various goal-directed behaviors. However, it remains unclear whether the incentive effects of social and material reward are supported by common or distinct neural circuits. Here, we have addressed this issue by quantitatively synthesizing and comparing neural signatures underlying social (21 contrasts, 207 foci, 696 subjects) and monetary (94 contrasts, 1083 foci, 2060 subjects) reward anticipation. We dem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
78
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 100 publications
(92 citation statements)
references
References 176 publications
(156 reference statements)
9
78
1
Order By: Relevance
“…Using a voxel-based meta-analytic method, we identified an extensive network of brain areas involved in the anticipation of social rewards. Our results consolidate findings from a previous coordinate-based meta-analysis (ALE) regarding the involvement of the basal ganglia, the midbrain, the dorsal anterior cingulate cortex, the supplementary motor area, the anterior insula and the occipital gyrus (Gu et al, 2019). However, thanks to the enhanced sensitivity of the AES-SDM meta-analytic method that we used, our results extend this network by including frontal, temporal, parietal and cerebellar regions that were not captured in the previous coordinatebased meta-analysis.…”
Section: Brain Regions Involved In the Anticipation Of Social Rewardssupporting
confidence: 89%
See 4 more Smart Citations
“…Using a voxel-based meta-analytic method, we identified an extensive network of brain areas involved in the anticipation of social rewards. Our results consolidate findings from a previous coordinate-based meta-analysis (ALE) regarding the involvement of the basal ganglia, the midbrain, the dorsal anterior cingulate cortex, the supplementary motor area, the anterior insula and the occipital gyrus (Gu et al, 2019). However, thanks to the enhanced sensitivity of the AES-SDM meta-analytic method that we used, our results extend this network by including frontal, temporal, parietal and cerebellar regions that were not captured in the previous coordinatebased meta-analysis.…”
Section: Brain Regions Involved In the Anticipation Of Social Rewardssupporting
confidence: 89%
“…These brain regions had not been previously identified in individual studies but have been suggested to participate in the brain processing of subjective value (Acikalin et al, 2017). In a similar previous AES-SDM meta-analysis of fMRI data from the MID task, the authors also identified a network of brain regions (largely overlapping with the brain region we identified here) showing decreases in the BOLD signal during the anticipation of monetary incentives (Wilson et al, 2018) that had not been identified in previous coordinate-based meta-analyses (Gu et al, 2019;Oldham et al, 2018b). Hence, our results neatly illustrate some of the advantages of the AES-SDM meta-analytic approach, including its increased sensitivity compared to the frequently underpowered single studies or coordinate-based meta-analyses .…”
Section: Brain Regions Involved In the Anticipation Of Social Rewardssupporting
confidence: 70%
See 3 more Smart Citations